ASSESSMENT OF BLOOD SERUM PROTEOME IN PATIENTS WITH SQUAMOUS CELL HEAD AND NECK CARCINOMA - G. V. Kakurina; I. V. Kondakova; E. L. Choinzonov; D. A. Shishkin; O. V. Cheremisina (Сибирский онкологический журнал, 2016)
We compared the serum proteome profiles of squamous cell head and neck carcinoma patients with metastases, without metastases and healthy volunteers using the combination of gradient gel-electrophoresis (1D-SDS PAGE) and mass-spectrometry. The study showed the difference in the serum proteome between healthy volunteers and squamous cell head and neck carcinoma patients with metastases and without clinical evidence of disease progression. Proteins in the serum proteome of patients with  squamous cell head and neck carcinoma that participate in various cellular processes can be suggested fur further study as potential markers of cancer progression.